Effects of tannins and Monensin in a feedlot diet on in vitro ruminal fermentation - Martello, Hariany Ferreira; De Paula, Nelcino Francisco; Macedo, Bruna Gomes; Zervoudakis, Joanis Tilemahos; Brutti, Danielle Dias; Carvalho, Perivaldo; Teobaldo, Ronyatta Weich [UNESP]; Da Silva Cabral, Luciano; Fonseca, Mozart Alves (Universidade Estadual de Londrina, 2019)
The objective of this study was to evaluate the effects of tannins versus Monensin on in vitro ruminal fermentation of a feedlot diet. The treatments were: control (no additives); low tannin (2 mg g DM-1); medium tannin (4 mg g DM-1), high tannin (6 mg g DM-1), and Monensin (0.02 mg g DM-1). The substrate was a feedlot diet composed by hay and concentrate (15:85 w/w; DM basis). Ruminal fluid was obtained from three rumen-cannulated male Santa Inês sheep. In vitro incubations were carried out during four consecutive weeks (run). Gas production (GP) was recorded at 1, 2, 3, 4, 5, 6, 8, 10, 12, 18, 24, 30, 36, 42, 48, 60, 72, 84, and 96 h of incubation. At 48 and 96 h, two bottles per treatment were withdrawn to measure pH, ammonia concentration (NH3) volatile fatty acid (VFA), in vitro dry matter digestibility (IVDMD), and in vitro neutral detergent fiber digestibility (IVNDFD). Addition of tannin or Monensin did not affect (P > 0.05) the kinetics parameters. Tannin supplementation reduced (P < 0.05) the GP at 24 h compared to Monensin. Addition of Monensin decreased (P < 0.05) IVDMD at 96 h and IVNDFD at 48 and 96 h compared to the control. The IVNDFD was lower (P < 0.05) with Monensin than with tannin at 48 and 96 h. The NH3 was lower (P < 0.05) with tannin compared with Monensin. By increasing tannin dosage, NH3 levels changed quadratically (P < 0.05). The inclusion of tannin in vitro reduced the NH3 concentration considerably when used in low dose.
Keywords: Additive; Beef cattle; Digestibility; Metabolism; Rumen